The Challenges of Implementing Industrial Revolution 4.0 Elements in TVET - Ngatiman, Suriani; Sulaiman, Tajularipin; Wong, Kai Yan (Journal of Technical Education and Training, 2023)
The advent of the industrial revolution 4.0 (IR4.0) impacted the national industry and the need to provide a highly skilled and competitive workforce. However, the previous study on the implementation of IR4.0 in vocational colleges in Malaysia is still unsatisfactory. Previous studies have also focused on Technical Education and Vocational Training (TVET) at the higher education. Therefore, this study conducted to explore the challenges towards the implementation of the IR4.0 element in the Vocational College (VC) curriculum. VC offers education skills certificate and diploma level to secondary school students. VC needs to be prepared to face this phenomenon in providing national human resources. The study employs qualitative design using in depth semi structured interview method guided by the interview protocol. Seven participants who met the sampling criteria were involved in this study. The Interview recording systematically managed and translated verbatim as interview transcripts. Then a thematic analysis performed using ATLAS.ti software (version 8) to construct appropriate codes, categories and themes to answer the research questions. The results of the interviews found five main challenges identified on the implementation of the IR4.0 element in the VC curriculum; curriculum review, providing teaching workforce, providing infrastructure, industry relations and engaging in education. Overall findings indicate the need for a revisit of the VC curriculum to implement the IR4.0 element and has implications to implement in providing a national workforce that meets the needs of the industrial demand. This study expected useful to Bahagian Pendidikan dan Latihan Teknikal Vokasional (BPLTV) in strengthening the Vocational Education Transformation agenda through the implementation of VC curriculum revisit by considering the challenges of IR4.0 implementation from various angles discussed to ensure students' knowledge and skills meet IR4.0 requirements to contribute to national development.